2016
DOI: 10.3390/separations3020016
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for the Characterization of Organic Residues from Stone Tools Using GC×GC-TOFMS

Abstract: Headspace solid-phase microextraction (HS-SPME) and gas chromatography-mass spectrometry (GC-MS) have traditionally been used, in combination with other analyses, for the chemical characterization of organic residues recovered from archaeological specimens. Recently in many life science fields, comprehensive two-dimensional gas chromatography-time-of-flight mass spectrometry (GCˆGC-TOFMS) has provided numerous benefits over GC-MS. This study represents the first use of HS-SPME-GCˆGC-TOFMS to characterize speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…A recent study by the authors demonstrated that the use of comprehensive two‐dimensional gas chromatography coupled to time‐of‐flight mass spectrometry (GC×GC‐TOFMS) afforded an increase in separation resolution and sensitivity when analysing these highly complex glues (Perrault et al . ). In addition, the headspace solid‐phase microextraction (SPME) enabled us to develop a sampling method that was as non‐destructive as possible (Hamm et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A recent study by the authors demonstrated that the use of comprehensive two‐dimensional gas chromatography coupled to time‐of‐flight mass spectrometry (GC×GC‐TOFMS) afforded an increase in separation resolution and sensitivity when analysing these highly complex glues (Perrault et al . ). In addition, the headspace solid‐phase microextraction (SPME) enabled us to develop a sampling method that was as non‐destructive as possible (Hamm et al .…”
Section: Discussionmentioning
confidence: 97%
“…A recent study by the authors demonstrated that the use of comprehensive two-dimensional gas chromatography coupled to time-of-flight mass spectrometry (GC×GC-TOFMS) afforded an increase in separation resolution and sensitivity when analysing these highly complex glues ). In addition, the headspace solid-phase microextraction (SPME) enabled us to develop a sampling method that was as nondestructive as possible (Hamm et al 2003;Regert et al 2006;Perrault et al 2016). However, HS-SPME coupled with traditional GC-MS (Hamm et al 2003;Regert et al 2006) is rather limited in both separation power and identification capabilities, which may hamper the identification of the numerous individual compounds of these complex organic mixtures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have determined that these archaeological adhesives and their associated components can contain various structural isomers across compound classes . This has been particularly emphasized for terpene and terpenoid compounds originating from plant origins .…”
Section: Introductionmentioning
confidence: 99%